Antimicrobial regional limb perfusion: Does it really fight infection?. (5th August 2020) - Rubio‐Martínez, L. M.
Summary: Over the last decades the use of antimicrobial regional limb perfusion (A‐RLP) has increased and A‐RLP is nowadays commonly used to treat orthopaedic infections by many equine practitioners. There have been a large number of studies published on the use of A‐RLP, many of which describe regional drug pharmacokinetics and clinical safety of the administration of different antimicrobials by A‐RLP. A limited number of studies describe the clinical use of A‐RLP as prophylactic or therapeutic treatment. However, despite being in use for 30 years there is still limited evidence about the efficacy of A‐RLP as a means to prevent and treat orthopaedic infections in horses.